1992
DOI: 10.1210/jcem.75.2.1639964
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin augments the sensitivity of MCF-7 human breast cancer cells to tamoxifen in vitro.

Abstract: Cultured MCF-7 human breast cancer cells were pre-exposed to either melatonin (232 ng/mL) or vehicle for 24 hrs prior to being washed and then re-exposed to either ethanol-vehicle or varying concentrations of tamoxifen (37.1 ng/mL, 3.71 micrograms/mL, 371 micrograms/mL) or melatonin (2.32 pg/mL, 232 ng/mL, 23.2 ng/mL) for 5 additional days. Only 371 ng/mL tamoxifen caused a 38% growth inhibition of cells pre-exposed to vehicle whereas all concentrations of tamoxifen inhibited the growth of melatonin pre-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 5 publications
1
27
0
2
Order By: Relevance
“…Several studies have demonstrated the antiproliferative role of melatonin using an MCF7 cell model to study the anti-estrogenic effect of this hormone (Hill and Blask, 1988;Wilson et al, 1992;Molis et al, 1994Molis et al, , 1995Lissoni et al, 1995). Estradiol was used in the present study to induce MCN increase in the testis to verify the effect(s) of melatonin on mast cell accumulation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have demonstrated the antiproliferative role of melatonin using an MCF7 cell model to study the anti-estrogenic effect of this hormone (Hill and Blask, 1988;Wilson et al, 1992;Molis et al, 1994Molis et al, , 1995Lissoni et al, 1995). Estradiol was used in the present study to induce MCN increase in the testis to verify the effect(s) of melatonin on mast cell accumulation.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, melatonin acts as an antiestrogen (Molis et al, 1994) since it inhibits the expression of estrogen-regulated genes (Molis et al, 1995), potentiates the sensitivity of MCF7 to tamoxifen (Wilson et al, 1992) and modulates the transcription of estrogen receptor in this cell line.…”
mentioning
confidence: 99%
“…One of the proposed properties of melatonin is its role as an oncostatic agent on hormone-dependent tumors. It has also been described that melatonin exerts antiproliferative effects on MCF7 cells, which has become a useful model to study the antiestrogenic effect of the pineal hormone (11,(32)(33)(34)(35). In synchronized MCF7 cells, both estrogen-dependent transcription and proliferation are inhibited by co-treatment with melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…The data which uphold this hypothesis are: (a) melatonin inhibits proliferation only in those cells expressing ERα (Cos & Sánchez-Barceló 2000a), (b) melatonin blocks the mitogenic effects of estradiol as well as counteracts the estradiol-induced invasiveness of MCF-7 cells (Cos et al 1998), (c) melatonin potentiates the sensitivity of MCF-7 cells to antiestrogens such as tamoxifen (Wilson et al 1992) or MDA-MB-231 cells (ERα negative) significantly enhances the growth-suppression effects of melatonin only in MCF-7 cells, that is to say, in those also expressing ER , and (e) melatonin inhibits the expression of estrogen-regulated genes such as pS2 or cathepsine (Molis et al 1995).…”
Section: Mechanisms Involved In the Effects Of Melatonin On Mcf-7 Cellsmentioning
confidence: 99%